Penilaian Kinerja Pengelolaan Limbah B3 di PT. X - Sabandar, Gilberth Frankrin; Nurvita Cundaningsih (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The management of hazardous and toxic waste requires compliance with technical requirements in order to prevent pollution and health hazards. This study was conducted to assess the level of compliance of B3 waste management at PT X through four main aspects, namely containment, sorting, facilities, and transportation, based on the provisions of the Minister of Environment and Forestry Regulation No. 9 of 2024, Permen LHK No. 6 of 2021, Permenhub No. 60 of 2019, and Permen LHK No. 1 of 2021. The research methods included direct observation at the location, interviews with relevant personnel, documentation of field conditions, and assessment of indicators using the Guttman method to measure compliance with technical requirements. The results of the study show that the facility aspect has a high level of compliance, namely 100%, because the safety facilities for evacuation route, ventilation, and storage buildings have met the standards. The transportation aspect scored 85% with the fulfilment of permit documents and the use of authorized third parties, although improvements are still needed in the physical condition of vehicles and container labelling. The sorting aspect achieved 50% because it was not fully carried out based on hazard characteristics. Containment was the lowest aspect with a score of 30% due to the use of non-waterproof containers without hazard symbols. Overall, the compliance rate of 66.25% indicates the need for significant improvement in the initial stages of management to achieve safe, effective, and regulatory-compliant hazardous waste management.